Assets and poverty status dynamics in 5 main regions in Indonesia - Purna Fitria (Universitas Islam Indonesia, 2017)
Comparing household expenditure and national poverty line, about 24.78% of households in Indonesia experienced poverty (expenditure below the poverty line) at least once within 14-year period. By utilizing the Ordered Logit Model, this study examines the determinants of household poverty status and analyses the relative effect of different household assets and characteristics on their poverty status. Employing three waves of Indonesia Family Life Survey (IFLS) consisting of household level data from the year of 2000, 2007 and 2014 and categorized households into five main regions based on their location. This study finds that assets (building, vehicle, jewellery, and savings) play important role in determining poverty status of households in Indonesia. Some demographic and socio-economic variables are confirmed to be statistically significant to poverty status in Indonesia. However, the determinants of poverty status vary within regions.